Plan publicitario para la empresa hotel palmar del sol, cantón Quevedo año 2015. - Rosado Vera, Kerly (2015)
The overall objective of this study aims to develop the advertising plan for the company Palmar del Sol Hotel Canton Quevedo; to achieve this goal we proceeded to perform the following methodology: 1) diagnosis of the current external environment (customers) of the company was conducted; 2) identification and evaluation of external and internal factors of the company Hotel Palmar del Sol was performed; 3) Preparation of the proposed strategic planning of the advertising plan considered action plan for the company. The study entitled "Commercial Plan for the company Palmar del Sol Hotel Canton Quevedo" consists of the following parts: Analysis of external factors, corresponding to factors that determine the current situation of advertising at local and provincial level, developed in level increase in visits; these forces allowed to show through analysis of the forces of Porter reality in the provision of good and service and faces against their competitors. To analyze this factor proceeded to evaluate, qualify and evaluate external factors identifying opportunities and threats through the SWOT matrix, the results are expressed in greater weight with the opportunities available to the company. In conclusion, the advertising plan has strategic objectives and actions, for this reason, the advertising plan has a tracking model in order to evaluate the development of appropriate activities and provide immediate solutions to the strategies proposed in the case of there are delays or inconveniences. Finally, the execution of the advertising plan is recommended, as it will raise the level of sales in each quarter during 2015.